Avaliação da atividade alelopática, antioxidante, fotoprotetora e análises fitoquímicas do extrato de folhas de Euterpe edulis Martius. - Mariquito, Anderson (2020)
Euterpe edulis Martius (Palmeira Juçara) is a native Brazilian palm (Arecaceae), about which there are very few reports regarding its biological activity and chemical composition. The objective of this research was to perform bioprospecting and evaluate t